Maternal-fetal determinants of infant body measurements at birth and neonatal survival - Flores, Emilie G.
The study evaluated the effects of maternal-fetal bio-social factors on infant body measurements at birth and neonatal survival. Survival rates? at different levels of selected maternal-fetal factors were also determined. It was participated in by 1998 mother-infant pairs from 14 lying-in Clinics (LIC) of the Manila Health Department. All mothers who delivered term alive normal babies from October to April 1989 were included in the study. On admission to the LIC, maternal physical measurements were means of personal interview. Infant body measurements were taken within 24 hours after birth. A month after birth, infants were followed up to evaluate their survival status and get additional data about the households. Using stepwise regression analysis, maternal weight-for-height, age of gestation and environmental sanitation were found to be significant predictors of both infant body measurements and neonatal survival. Parity, maternal education, height, and mid-upper arm circumference (MUAC) positively influenced body measurements but not neonatal survival. Birth weight, length, MUAC, Ponderal index and MUAC/head circumference (HC) affect neonatal survival. Overall neonatal survival rate was 97.1%. When cut-off points of at least 2500 g for birth weight, at least 48 cm length, at least 9.5 cm MUAC, at least 32 cm head or chest circumference were used, the resulting neonatal survival rate was at least 98.5%. These results are consistent with the recommendation of the World Health Organization (WHO) used in the Philippines. Survival rates below the WHO recommended cut-off points were 50 to 88%. When maternal weight-for-height of at least 90% of standard, at least 152 cm height and at least 22.5 cm M-MUAC were used, the noenatal survival rates was also at least 98.5%. The findingd can help clinicians and health workers in screening who among mothers should be referred to hospitals or who can avail themselves of the domicialary services. Birth length and MUAC under field conditions can be utilized as alternative indicators of birth weight to screen at risk infants. Knowledge of the bio-social predictors and alternative indicators can allow efficient risk assessment and referral of infants who needs special care. The results can also aid in preparing medical and nutrition plans duringpre- and post-natal care to improve birth outcome.